NuttX remote client: Implementación de un cliente para protocolos de distribución remota para el NuttX RTOS. - Rojas-Vargas, Jose Pablo (Instituto Tecnológico de Costa Rica, 2012)
This paper presents the study of the implementation for a new feature that can access files in a local area network. The project is focused on a protocol for remote data distribution which takes a special file system, and when it is installed, network information is required to operate. Once this happens and it’s connected to a server, it can be used from the embedded board with the operating system as any local file. The chosen protocol was developed by Sun Microsystems, whose name is (NFS) "Network File System", which allows a client user to access files on a local network like a similar manner of accessing the local storage. The development of the project was based on the source code of the FreeBSD operating system and OpenBSD for the new role of NFS, because it has a permissive free software license to use these codes in NuttX RTOS. These two operating systems are open source distributions owned by BSD or "Berkeley Software Distribution", operating system derived from the UNIX system, which arises from the contributions made by the University of California at Berkeley. At the end of project, it was achieved the Implementation of a NFS client for NuttX RTOS, which lets you access remote files as if they were local, making at least the basic operations of the NFS protocol and obtaining a design focused on the use optimal memory because the network file system always uses a constant value equal to 2192 kBytes memory.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2012.
Keywords: NFS; RPC; VFS; NuttX RTOS; NSH